Nudging towards Sleep-Friendly Health Care: A Multifaceted Approach on Reducing Unnecessary Overnight Interventions - Kadura, Sullafa; Eisner, Lauren; Lopa, Samia H.; Poulakis, Alexander; Mesmer, Hannah; Willnow, Nicole; Pigeon, Wilfred R. (Applied Clinical Informatics, 2024)
Background Choice architecture refers to the design of decision environments, which can influence decision-making in health care. Nudges are subtle adjustments in these environments that guide decisions toward desired outcomes. For example, computerized provider order entry within electronic health records (EHRs) recommends frequencies for interventions such as nursing assessments and medication administrations, but these can link to around-the-clock schedules without clinical necessity.Objectives This study aimed to evaluate an intervention to promote sleep-friendly practices by optimizing choice architecture and employing targeted nudges on inpatient order frequencies.Methods We employed a quasi-experimental interrupted time series analysis of a multifaceted, multiphase intervention to reduce overnight interventions in a hospital system. Our intervention featured EHR modifications to optimize the scheduling of vital sign checks, neurological checks, and medication administrations. Additionally, we used targeted secure messaging reminders and education on an inpatient neurology unit (INU) to supplement the initiative.Results Significant increases in sleep-friendly medication orders were observed at the academic medical center (AMC) and community hospital affiliate (CHA), particularly for acetaminophen and heparin at the AMC. This led to a reduction in overnight medication administrations, with the most substantial impact observed with heparin at all locations (CHA: 18%, AMC: 10%, INU: 10%, p < 0.05). Sleep-friendly vital sign orders increased significantly at all sites (AMC: 6.7%, CHA: 4.3%, INU: 14%, p < 0.05), and sleep-friendly neuro check orders increased significantly at the AMC (8.1%, p < 0.05). There was also a significant immediate reduction in overnight neurological checks performed at the AMC.Discussion Tailoring EHR modifications and employing multifaceted nudging strategies emerged as promising approaches for reducing unnecessary overnight interventions. The observed shifts in sleep-friendly ordering translated into decreases in overnight interventions.Conclusion Multifaceted nudges can effectively influence clinician decision-making and patient care. The varied impacts across nudge types and settings emphasizes the importance of thoughtful nudge design and understanding local workflows.
Keywords: choice architecture; clinical decision support; electronic health record; inpatient sleep; nudges